THE INFLUENCE OF HUMAN RESOURCE DEVELOPMENT AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT RUPA AESTETIKA TEKNOLOGI AKTUAL: THE INFLUENCE OF HUMAN RESOURCE DEVELOPMENT AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT RUPA AESTETIKA TEKNOLOGI AKTUAL - Akfilni, Dina Akfilni; Hasanah, Hasanah (PENANOMICS: International Journal of Economics, 2025)
The purpose of this study is to determine and analyze the influence of human resource development and the work environment together on the performance of employees of PT Rupa Aestetika Teknologi Aktual. This research can be categorized as associative research, aiming to determine the relationship between several variables. It uses primary and secondary data. The sample size is 47 employees or respondents. Data analysis used is data quality testing with validity and reliability tests, followed by classical assumption testing with normality tests, heteroscedasticity tests, and multicollinearity tests. Data analysis techniques include multiple linear regression analysis and the coefficient of determination. Finally, hypothesis testing is performed using the t-test and F-test. The results of this study vThe variables of human resource development and work environment together have a positive and significant influence on the performance of employees of PT Rupa Aestetika Teknologi Aktual, because the F value count of 714.313 where the F value count greater than F table of 714,313 > 3,093.